Beyond the Disease: Contextualized Implications of the COVID-19 Pandemic for Children and Young People Living in Eastern and Southern Africa - Kaymarlin Govender; Richard Gregory Cowden; Patrick Nyamaruze; Russell Murray Armstrong; Luann Hatane (Frontiers Media S.A., 2020)
The coronavirus disease 2019 (COVID-19) pandemic has created extraordinary challenges and prompted remarkable social changes around the world. The effects of COVID-19 and the public health control measures that have been implemented to mitigate its impact are likely to be accompanied by a unique set of consequences for specific subpopulations living in low-income countries that have fragile health systems and pervasive social-structural vulnerabilities. This paper discusses the implications of COVID-19 and related public health interventions for children and young people living in Eastern and Southern Africa. Actionable prevention, care, and health promotion initiatives are proposed to attenuate the negative effects of the pandemic and government-enforced movement restrictions on children and young people.